Pengaruh current ratio, net profit margin, total asset turnover, debt to equity ratio dan return on asset Terhadap Pertumbuhan Laba Pada Perusahaan Sektor Batubara di Bursa Efek Indonesia Periode 2016-2020 - Hasibuan, Rahmawaty; Situmorang, Martalina (Universitas Sari Mutiara Indonesia, 2022)
The purpose of this research was to determine the effect of Current Ratio (CR), Net Profit Margin (NPM), Total Asset Turnover (TATO) Debt to Equity Ratio (DER), and Return On Assets (ROA) on partial profit growth at Sector Batubara. Beverages listed on the Indonesia Stock Exchange in 2016-2020. The number of samples in this research were amounted to 11 companies during the research period of 5 years so that it has observational data of 55 samples. The analysis technique used is multiple linear regression. The results showed that the Current Ratio had no significant effect on profit growth, Net Profit Margin had no significant effect on profit growth, Total Asset Turnover had a significant effect on profit growth, Debt to Equity Ratio had a significant effect on profit growth, Return On Assets had a significant effect on profit growth. Collectively the Current Ratio (CR), Net Profit Margin (NPM), Total Asset Turnover (TATO), Debt to Equity Ratio (DER) and Return On Assets (ROA) variables simultaneously have a significant effect on profit growth.